Performance study on dissolved air flotation (DAF) unit and process performance improvement study in the physicochemical treatment of wastewater - Lee, Seng Chow (2007)
From the time of the early 20th century, Dissolved Air Flotation (DAF) had been used in the separation process. In the DAF system, air is dissolved in the wastewater under a pressure of several atmospheres, followed by release of the pressure to the atmospheric level. In this case, the recycle flow system has been studied. For this kind of system, a portion of the DAF effluent is being recycled, pressurized and semi-saturated with air. The main study object is the DAF System in HACO Asia Pacific Sdn. Bhd. In the first stage, process performance improvement study was carried out to determine the most effective operating parameters and conditions of the DAF. Then, a performance monitoring study was continued by operating the DAF in the most effective and optimum condition. Samples were being taken before and after the DAF treatment to determine its pollutant removal efficiency. Results from the performance monitoring study showed that the DAF is able to meet its original design specification of Total Suspended Solids (TSS) removal efficiency up 85%-95%. At a later stage, an emerging design system known as Band-pass Filter (BF) was brought in for a comparative performance study with the DAF system. The BF is intended for mechanical filtering of wastewater in situations where rejections of waste products in connection with processing plants are required. To obtain optimum cleansing, the BF is tuned for the imminent cleansing process. Results from the comparative performance study showed that the BF can achieve a slightly higher average TSS and Chemical Oxygen Demand (COD) removal efficiency, with 93.9% and 49.6% respectively. On the other hand, DAF can achieve a slightly higher average Oil and Grease (O&G) removal efficiency up to 91.9%.